Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0236371
|View full text |Cite
|
Sign up to set email alerts
|

Flow and hydrodynamic shear stress inside a printing needle during biofabrication

Abstract: We present a simple but accurate algorithm to calculate the flow and shear rate profile of shear thinning fluids, as typically used in biofabrication applications, with an arbitrary viscosity-shear rate relationship in a cylindrical nozzle. By interpolating the viscosity with a set of power-law functions, we obtain a mathematically exact piecewise solution to the incompressible Navier-Stokes equation. The algorithm is validated with known solutions for a simplified Carreau-Yasuda fluid, full numerical simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…We find that the rheological parameters ( η 0 , τ, δ ) of the suspension medium obtained this way closely agree with cone-plate rheology measurements 34 . Moreover, the velocity profile for different pressure values can be accurately predicted (SI Fig.…”
Section: Methodssupporting
confidence: 81%
“…We find that the rheological parameters ( η 0 , τ, δ ) of the suspension medium obtained this way closely agree with cone-plate rheology measurements 34 . Moreover, the velocity profile for different pressure values can be accurately predicted (SI Fig.…”
Section: Methodssupporting
confidence: 81%
“…Additionally, depending on the geometry of the inkjet needle, very high shear forces can be generated here, which might influence the final cell response in 3D. 116 As cells are fillers with highly nonlinear mechanical properties, 18,[107][108][109] we found that they can significantly affect the final mechanical properties of the biofabricated construct. This has already been shown in a previous study on fibrous collagen-based hydrogels, which shifted their mechanical properties from compression softening to compression stiffening and thereby, reversed their compression-tension asymmetry by the addition of cells.…”
Section: Cell Embedding In Biofabrication Can Alter the Final Hydrogementioning
confidence: 85%
“… 2017 ; Müller et al. 2020 ). How exactly these hydrodynamic forces correlate with cell deformation, however, strongly depends on the elastic behavior of the cell and its interaction with the flowing liquid.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in this process lies in the control of large cell deformations and cell damage during printing. Those deformations arise from hydrodynamic stresses in the printer nozzle and ultimately affect the viability and functionality of the cells in the printed construct (Snyder et al 2015;Blaeser et al 2015;Zhao et al 2015;Paxton et al 2017;Müller et al 2020). How exactly these hydrodynamic forces correlate with cell deformation, however, strongly depends on the elastic behavior of the cell and its interaction with the flowing liquid.…”
Section: Introductionmentioning
confidence: 99%